Investigation of properties for the commun compounds employed in Photovoltaics - D. BENABDELAZIZ; S. BERRAH; N.BOURAHLA; A. BOUKORTT (University of Eloued, 2019)
The III-V semiconductors are the most used compounds high-efficiency for solar cells, In this work we aim, to study the structure and band structure properties for Indium–V semiconductor, The development of new model of solar cells from those semiconductors materials are very promising technology to give high conversion efficiency. To investigate the electronic and optical properties of binary compounds Indium -V (InAs, In Sb, InN and InP) in Zinc blend structure we have used the density functional theory (DFT), with Full-potential linearized Augmented Plane Wave. For exchange and correlation energy treatment we employed the local density approximations (LDA) as proposed by Wang and Pedrew and the generated gradient approximation (wc-GGA) from Wu and Cohen to calculate the accurate band structure we used the mBjexchange potential. These results show that those materials have wide range of bandgap and that its hold promise for the potentiel application in optoelectronic devices as a results we have found that thoses materials could convert these structures capable of converting wavelength between [810 nm and 3500 nm ] from solar spectrum into electrical energy. Furthermore, we could have very interesting material by making alloys with those binary compounds
Intervention
Keywords: Solar cell; FP-LAPW; mBJ; III-V semiconductor